Experimental and numerical investigation of impinged water jet effects on heated cylinders for convective heat transfer - Alnak, Dogan E.; Varol, Yasin; Firat, Mujdat; Öztop, Hakan Fehmi; Ozalp, Coskun (Elsevier France-Editions Scientifiques Medicales Elsevier, 2019)
Effect of jet flow structures impinged on a heated cylinder has been investigated experimentally and numerically in this study. The FLUENT 6.3.26 was used to simulate this numerical problem. In the numerical section, the influence of some variables such as the distance between cylinder and jet on the fluid flow characteristics has been analyzed. The distance between the cylinders and jet has been varied as H/S = 4, 6, and 10. The flow characteristics around the heated cylinder with a diameter of 30 mm were obtained in the range of 5000 <= Re-D <= 20000. Variations of velocity and temperature profiles on the cylinder have been determined for increasing Reynolds Number. Techniques of high image velocimetry will be employed throughout the investigations to obtain two-dimensional velocity field distributions. Rectangular nozzle jet flow is achieved with a size of 30 mm x 390 mm. The experiments are performed in a large scale water channel and obtained experimental results are compared numerical results for three different Reynolds number of 5000, 7500, and 10000 based on cylinder diameter. The results showed that the heat transfer decreased with the increase in the H/S value. Especially the decline in high H/S values took place linearly. The increase in H/S values decreased the impact of the first cylinder on the second cylinder. The increase in Reynolds number also increases the heat transfer.
Keywords: PIV; Jet flow; Heated cylinder; Turbulent flow